Impacts of small mammals and birds on low-tillage, dryland crops - Sterner, Ray T; Petersen, Brett E; Gaddis, Stanley E; Tope, Kenneth L; Poss, David J (Crop protection, 2003)
During 2000–2001, small mammals, birds, and potential corn/soybean damage were studied at a low-tillage, non-irrigated agricultural research site in the Colorado Piedmont. A small mammal survey involved four trapping sessions and 18, 12-live-trap grids each. Within years, two grids each were placed at random, fixed locations in experimental corn, fallow, millet, pea, soybean, sunflower, and wheat plots at the site; two off-plot grids each were set at random, fixed locations <100 m from the north and south edge of these plots. In 2001, periodic bird observations were conducted, and damage to corn and soybean plants was assessed. Capture rates were low during all trap sessions (range 0.1%–3.3%, X ̄ =2.2% ). Sixty-three small mammals were captured and 39 were recaptured. Captures included deer mouse ( Peromyscus maniculatus), northern grasshopper mouse ( Onychomys leucogaster), thirteen-lined ground squirrel ( Spermophilus tridecemlineatus), and western harvest mouse ( Reithrodontomys megalotis). Deer mice accounted for 56 of the initial captures (88.9%). In-crop captures ( n=15) and recaptures ( n=16) were most frequent in wheat plots. Bird counts were low and included horned lark ( Eremophila alpestris), killdeer plover ( Charadrius vociferus), lark bunting ( Calamospiza melanocorys), mountain plover ( Charadrius montanus), mourning dove ( Zenaida macroura), and western meadowlark ( Sturnella neglecta). No direct seed removal, sprout removal, or plant clipping by small mammals or birds was observed, but some clipping of soybean plants was attributed to deer ( Odocoileus virginianus and O. hemionus) and jack rabbits ( Lepus townsendii or L. californicus). Plant debris accumulation is viewed as a key factor determining small mammal abundance and potential damage in low-till agriculture.